ҚАРАҚАЛПАҚ ТИЛИНИҢ ТҮСИНДИРМЕ СӨЗЛИГИНДЕ ОМОНИМ СӨЗЛЕРДИҢ БЕРИЛИЎИ - Мамбетмуратова, М.Т. (FAN va JAMIYAT, 2020)
The spelling dictionary of the Karakalpak language speaks about the giving of homonymous words, attention to their meanings and etymology.